1990
DOI: 10.1148/radiology.177.3.2243976
|View full text |Cite
|
Sign up to set email alerts
|

Acute splenic sequestration crisis in two adults with sickle cell disease: US, CT, and MR imaging findings.

Abstract: Acute splenic sequestration crisis (ASSC) is a rare complication in adults with sickle cell disease that is diagnosed clinically by means of sudden splenic enlargement and a rapid fall in hematocrit. Two cases of ASSC in adults with heterozygous sickle cell disease (sickle cell-thalassemia and sickle cell-hemoglobin C disease) were studied with use of duplex Doppler ultrasound (US), computed tomography (CT), and magnetic resonance (MR) imaging. In both cases, US showed patency of the splenic vein and multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Low-attenuation peripheral areas are seen at CT (Fig 21). In one study of two adult patients, the spleen showed high signal intensity at T1-and T2-weighted MR imaging, compatible with hemorrhage, which was confirmed in one patient (67). …”
Section: The Spleenmentioning
confidence: 75%
“…Low-attenuation peripheral areas are seen at CT (Fig 21). In one study of two adult patients, the spleen showed high signal intensity at T1-and T2-weighted MR imaging, compatible with hemorrhage, which was confirmed in one patient (67). …”
Section: The Spleenmentioning
confidence: 75%
“…One of the unique features of SCA in Eastern Saudi Arabia is persistence of splenomegaly and preservation of splenic function well into adulthood [2,3]. This, however, predisposes them to complications such as hypersplenism, splenic sequestration crisis, and splenic abscess which are rarely seen in African adults with SCD [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…However, acute complete splenic infarction is extremely rare [15] . There are a few reports about acute complete infarction of the spleen, one of them developing in a wandering spleen [16] , while another is due to acute splenic sequestration crisis in 2 adults with sickle cell disease [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Splenic infarct typically appears on sonography as wedge-shaped, hypoechoic and well-demarcated lesions [1,19] . If the reason is splenic vein thrombosis, it results in splenomegaly [17] .…”
Section: Discussionmentioning
confidence: 99%